Lemma and palea micromorphological study of Setaria species (Poaceae) in Iran - Keshavarzi, Maryam; Mosaferi, Samaneh; Hosseini, F. (Acta Biologica Szegediensis, 2024)
Setaria (Poaceae, Paniceae, Cenchrinae) comprises 136 species worldwide and 3 species in Iran. This weedy grass is distributed in various parts of the world. In this study, the characters of the lemma and palea of 9 populations of Setaria were studied micromorphologically using a scanning electron microscope (SEM) to identify diagnostic characters for the delimitation of the studied species. A total of 18 qualitative and quantitative characters of the lemma and palea surfaces were considered. Different shapes of microhairs, epicuticular wax, and the occurrence of cork cells and silica cells were evident in the studied taxa. The results of this study revealed the taxonomic value of floret micromorphological characters in Setaria species.